Osteochondral Allograft Transplant of the Patella Using Femoral Condylar Allografts: Magnetic Resonance Imaging and Clinical Outcomes at Minimum 2-Year Follow-up. Issue 10 (28th October 2020) - Lin, Kenneth M.; Wang, Dean; Burge, Alissa J.; Warner, Tyler; Jones, Kristofer J.; Williams, Riley J.
Background: Fresh osteochondral allograft transplant (OCA) has good outcomes in the knee. However, donor tissue for patellar OCA is limited. Outcomes after nonorthotopic OCA of the patella using more readily available femoral condylar allograft (FCA) tissue have not been previously reported. Purpose: To assess short-term magnetic resonance imaging (MRI) and minimum 2-year clinical outcomes of nonorthotopic patellar OCA using an FCA donor. Study Design: Case series; Level of evidence, 4. Methods: A prospective institutional cartilage registry was reviewed to identify patients treated with patellar OCA using an FCA donor between August 2009 and June 2016. OCA plugs were obtained from the FCA at its trochlear-condylar junction and implanted into the recipient patellar lesion. Early postoperative MRI scans were graded by a blinded musculoskeletal radiologist using the Osteochondral Allograft MRI Scoring System (OCAMRISS). International Knee Documentation Committee Subjective Knee Evaluation Form (IKDC), Knee Outcomes Survey–Activities of Daily Living (KOS-ADL), and pain visual analog scale (VAS) scores were collected preoperatively and at minimum 2 years postoperatively, and outcomes were compared using the paired t test. Results: A total of 25 patients were included for clinical outcome analysis and 20 patients for MRI analysis. MRI scans obtained at a mean of 11.4 months (range, 6-22 months) postoperatively showed a mean total OCAMRISS score of 9.0 (range, 7-11); mean bone, cartilage, and ancillary subscores were 2.6, 3.7, and 2.6, respectively. At the latest follow-up (mean, 46.5 months; range, 24-85 months), postoperative improvements were noted in IKDC (from 45.0 to 66.2; P = .0002), KOS-ADL (from 64.3 to 80.4; P = .0012), and VAS (from 5.1 to 3.4; P = .001) scores, with IKDC and KOS-ADL scores above the corresponding previously reported minimal clinically important difference. Conclusion: In this study, patellar OCA using nonorthotopic FCA led to significant short-term improvements in pain and patient-reported outcomes. The majority of nonorthotopic patellar grafts demonstrated full osseous incorporation and good restoration of the articular surface on MRI at short-term follow-up.